1984
DOI: 10.1016/0378-1135(84)90063-4
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus infection of the bovine respiratory tract

Abstract: Two viruses, morphologically resembling coronaviruses and antigenically indistinguishable from bovine enteric coronavirus, were isolated in bovine tracheal organ cultures from the lungs and trachea of young calves with respiratory disease. Intranasal and intratracheal inoculation of these viruses into neonatal calves resulted in a predominantly upper respiratory tract infection, which was associated with the development of mild respiratory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
1
5

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 7 publications
1
56
1
5
Order By: Relevance
“…6,9,14,18 It has been difficult to fulfill Koch' s postulates in regard to BCV involvement in respiratory problems such as BRDC because of limitations of these postulates to deal with host and environmental interactions and polymicrobial infections. 3 Nevertheless, a preponderance of evidence 7,8,9,11,14,17,18 now suggests that this virus may likely be implicated in BRDC by predisposing cattle to induction of respiratory tract disease and poor health performance. If this is the case, a clear understanding of BCV epidemiologic characteristics and its role in disease causation under field conditions is necessary for development of preventive measures such as vaccination prior to shipping to control this pathogen in feedlots calves.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…6,9,14,18 It has been difficult to fulfill Koch' s postulates in regard to BCV involvement in respiratory problems such as BRDC because of limitations of these postulates to deal with host and environmental interactions and polymicrobial infections. 3 Nevertheless, a preponderance of evidence 7,8,9,11,14,17,18 now suggests that this virus may likely be implicated in BRDC by predisposing cattle to induction of respiratory tract disease and poor health performance. If this is the case, a clear understanding of BCV epidemiologic characteristics and its role in disease causation under field conditions is necessary for development of preventive measures such as vaccination prior to shipping to control this pathogen in feedlots calves.…”
mentioning
confidence: 95%
“…4,9 The nasal route of transmission is speculated to occur in addition to the fecal-oral route. 2 The role of BCV as a pathogen of the respiratory tract in calves [10][11][12][13] and feedlot cattle is not completely defined. Several investigators have shown that BCV may be implicated in BRDC, 6,8,9,[14][15][16][17][18] with decreased growth performance in feedlot cattle 4,5,7 ; others have found no correlation between BCV shedding and respiratory tract disease under field conditions 4,5 ; some have failed to reproduce respiratory tract disease after experimental inoculation of calves with BCV [19][20][21] ; and others have isolated this virus from healthy cattle 22 or have not detected BCV shedding in all feedlot calves with respiratory tract disease.…”
mentioning
confidence: 99%
“…Calves around 3 months of age may also present pathological processes of upper respiratory tract caused by BCoV (Mcnulty et al 1984, Heckert et al 1990, Heckert et al 1991, Tsunemitsu et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…1 Bovine coronaviruses are generally not associated with severe lower respiratory disease. 1,3 The Minnesota isolate produced a severe, clearly defined lower respiratory disease (Kapil S, Pomeroy K, Goyal SM, et al: 1990, Abstr 31st Ann Mtg North Central Conf Vet Lab Diagn) later in the infection (5-9 days postinfection) and was the cause of death in 1 calf. Blood was present in feces of these calves for l-2 days starting 4 days after infection.…”
mentioning
confidence: 99%